Gestión sostenible del aceite mineral usado en los establecimientos de lubricación de vehículos del cantón el Empalme, provincia de la Guayas - Villanueva Conforme, Genesis Manuela (2021)
Used oil is one of the hazardous wastes that occur in greater quantity due to the increase in the number of vehicles, often making it difficult for the generators of this hazardous waste to properly manage it. The present investigation of type diagnostic and exploratory was developed with the aim of promoting the sustainable management of mineral oils used in vehicle lubrication establishments in the canton of El Empalme, for the development of this project a diagnosis of current management was carried out of used oil where the observation method was used to identify the existing establishments, find out how they provide the service after that, all the owners of the existing lubricators were interviewed and a control of the amount of used oil generated was maintained per day from which an approximate volume of 664.92 gallons per month and 7,979.04 gallons per year of used oil was obtained in the canton. A training plan on hazardous waste was also carried out for 33 people, including owners with workers, where various topics were taught in 2 months using the explanatory method. Finally, a proposal was made for a correct management of used oil from the collection until final disposal. With the results obtained, it is concluded that the used oil is not being managed correctly in its entirety since only 10 lubricators deliver it to the company BIOFACTOR S.A for its subsequent management. The RStudio statistical program allowed analyzing the behavior in the generation of used oil by each establishment and measuring the level of knowledge acquired by the participants in the training, which was favorable since they reached a high and medium-high level. KEYWORDS: Environmental Manager, Hazardous Waste Generator Registry, Environmental Regulations, lubricators, used oil.